Heat Transfer Across Tube Banks With A Passive Control Vortex Generator In Steady One-Directional And Oscillatory Flows - Mohd Saat, Fatimah Al Zahrah; Sukri, Mohamad Firdaus; Shikh Anuar, Fadhilah; Akop, Mohd Zaid; Lin, Chou Aw; Abdul Manan, Zainuddin (Penerbit Akademia Baru, 2021)
Fluid can flow in one-directional (normal flow) or oscillatory conditions. Fluid flow in some energy system involved oscillatory flow condition. The use of vortex generator has been proven to improve heat transfer in the case of one-directional flow but the impact of vortex generator in oscillatory flow condition is yet unknown. This study focusses on the heat transfer performance across a heated tube banks using a Computational Fluid Dynamics (CFD) model. Two flow conditions were modelled: steady one-directional and oscillatory flow conditions. Two-dimensional CFD models of steady flow and oscillatory flow were solved using the SST k-ω turbulence model for two different cases of heated tube banks with and without the vortex generators. The heat transfer performance for both flow conditions were analysed by considering a heat transfer parameter known as Colburn-j factor. Results showed that the use of a vortex generator increased the heat transfer enhancement, regardless of the flow conditions. However, it is also noted that the heat transfer behaviour in a steady flow and an oscillatory flow is not the same, especially with the appearance of secondary flows in the system. The difference is discussed with respect to dimensionless quantity of Colburn j-factor, the non-dimensionless quantity, and the amplitude of temperature field. The result indicates that the heat equation in the steady flow condition is not very suitable to be directly used in oscillatory flow conditions. Appropriate heat equation needs to be properly addressed for situations that involve oscillatory flow motion